PENGARUH OWNER’S EXPERTISE PADA BUSINESS PERFORMANCE DENGAN DIMODERASI INNOVATION PADA USAHA KECIL MENENGAH (UKM) - Anggun Kurnia Saraswati; Asri Laksmi Riani (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2016)
The purpose of this study was to examine the influence of Owner’s Expertise on Businnes Performance and Innovation as a moderating. The existence of previous studies that only examine the relationship between the Owner's Expertise in Performance Businnes motivate researchers to conduct research by adding a moderating variable as a development of previous research. Samples were taken of 100 batik artisans in Surakarta, Sragen, Karanganyar & Lasem. The sampling technique with purposive sampling method. To determine the effect may moderate the influence of Innovation whether Owner's Expertise on Performance Businnes used MRA analysis (Moderating Regression Analysis). The results of this study indicate that the Owner's Expertise significant effect on Businnes Performance, but had no significant effect Innovation as a moderating.